Timing of progesterone luteal support in natural cryopreserved embryo transfer cycles: back to basics. Issue 1 (July 2022) - Mizrachi, Yossi; Weissman, Ariel; Rozen, Genia; Rogers, Peter A.W.; Stern, Catharyn; Polyakov, Alex
Abstract: Moderate quality evidence suggests that the administration of progesterone luteal phase support (LPS) is beneficial in natural and modified (HCG-triggered) natural frozen embryo transfer (FET) cycles. No comparative studies examining the optimal timing of progesterone LPS administration in natural FET cycles have been conducted, and the common practice differs greatly between clinics worldwide. In the absence of clinical trials, we aimed to provide a scheme for progesterone supplementation in an attempt to mimic its natural secretion by the corpus luteum. On the basis of early studies of ovulation physiology, we suggest that progesterone luteal support administration in natural FET cycles should start 36 h after the onset of the LH surge when measured in a morning serum test, or 36 h after the administration of HCG for triggering final follicular maturation. Blastocyst transfer should be carried out after 5 full days of progesterone supplementation. Randomized clinical trials are required to confirm these recommendations.